Dysfunctional Families: A Study in Flannery O’Connor’s “A Good Man is hard to Find” and “Good Country People” (Journal of the College of Basic Education, 2022)
Flannery O’Connor is one of the great short stories writers of the twentieth century. She wrote about southern life. She reflects a theme that became well-known in most of the modern works, which is the dysfunctional family. It is the sense of vanity and disobedience that leads to dysfunctional families that became a modern age phenomena.In “A Good Man is Hard to Find” one can find the self- reliant individualو the Baily, his kids and the grandmother. No one seems to pay any attention to the grandmother’s fears or suggestions, it is only her cat that gives her the sense she is not alone. In ‘Good Country People’ O’Connor’s other short story that deals with a prideful individual ‘Joy Hopefull’, with her fits of rage, she reveals an image of dysfunctional family. Challenging her mother who treats her as still a young child, Joy changes her name to Hulga. Breaking with her mother and the traditions, Hulga became an easy prey to a deceiving Bible salesman.